Letter from Henry Carrington Bolton to James Curtis Booth, June 4, 1883 - Bolton, Henry Carrington (1883)
Henry Carrington Bolton (1843-1903), an American chemist, professor of science at Trinity College, and relative of James Curtis Booth (1810-1888), writes to Booth, mentioning his fatigue from proofreading his Catalogue of Scientific and Technical Periodicals and his plans to sail for Liverpool on the S.S. Baltic with a view to seeing Scotland.
Keywords: Booth, James Curtis, 1810-1888; Bolton, Henry Carrington, 1843-1903